Community Satisfaction to Corporate Social Responsibility (CSR) Programs for Rural Economic Empowerment - Sugiarto, Mochamad; Sulaiman, Adhi Iman (Technium Social Sciences Journal, 2021)
This study aims to analyzing the implementation of a cement manufacturer’s CSR programs to improve effectiveness and satisfaction of people in general. The research conducted using survey method to 86 respondents, who are members of Joint Business Group in Cilacap Regency and beneficiaries of Corporate Social Responsibility (CSR) programs. The data were collected through observation, questionnaires, interviews and discussions, then used descriptive statistical analysis and qualitative narrative. The research results have found that the company’s direct involvement model in a CSR program gives several advantages. Nevertheless, the limited quantity and quality of this cement manufacturer’s CSR administrators result in less effective planning, assistance and evaluation processes. People are satisfied with how the CSR is executed by the cement manufacturer, yet the program they carry out has not completely matched what these people need and cannot correctly identify the CSR program beneficiary targets. In relation to this, the implementation of CSR using direct involvement model needs some improvement to make it more effective and intensive. The modification of direct involvement model by use of information technology becomes an important alternative to deal with the limited quantitaty and quality of human resources of CSR program administrators.